Study of the Social Ministry of Some Charismatic Churches in Ghana: A Case Study of the Provision of Educational and Healthcare Services by Four Selected Churches - Eshun, D. (University of Ghana, 2013)
The research sought to investigate the social ministry of four selected Charismatic churches in Ghana. Specifically, it examined the underlying factors influencing the current interest of these Charismatic churches‟ contribution towards the development of education and healthcare services in Ghana. Charismatic churches‟ interest in social ministry is problematized due to the fact that in the past social ministry did not appear as a prominent feature in the ethos of Charismatic Christianity in Ghana. The social ministry of churches in Ghana can however be traced to the early European missionary enterprise that combined evangelization with the development of formal education and the introduction of Western medicine among others. The research adopted the historical and phenomenological approaches as the methodologies for the study. Findings of the study were analyzed within the mission theological concept of diakonia. Data was gathered mainly through personal interviews with the church founders, associate pastors, church members and through participant observation in their social ministry programmes. Among other things the research revealed that, the underlying factors influencing the selected Charismatic churches‟ social ministry include the example set by the mainline churches, their re-reading of the Bible, the need to empower their members and their quest to become socially relevant. The study also revealed that what Charismatics refer to as faith healing has been redefined to include the use of medicine, whilst access to healthcare has also been made relatively easier for their members. Finally, the study also revealed that Charismatic churches‟ involvement in social ministry is a growing phenomenon. The researcher among other issues recommends that measures should be undertaken to ensure that the educational and scholarships programmes of these churches are expanded and made more accessible to cater for the poor and underprivileged in society. In the area of healthcare, administrative measures should be put in place to ensure that the healthcare programmes continue to operate long after the founders (pastor-doctors) are no longer on the scene. Church members should also regularly demand accountability and transparency regarding the operations of the social ministry to inspire confidence in the programmes. Founders of these Charismatic churches should also give the social ministry of their respective churches the free hand to operate without unnecessary interference, and the church members must be made to feel ownership of the programmes to ensure their continuous support. In conclusion the research posits that the selected Charismatic churches re-reading of the Bible, the socio-economic challenges of the times and the quest to remain socially relevant among others has accounted for these changes.
Thesis (MPHIL)-University of Ghana, 2013